Behaviorist-Based Tahsin Learning: Strengthening Tajwid Awareness through the Tahsin Bagdadi Method - Kalsum, Umi; Rahmawati, Sri Tuti; Syarif, Fajar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The low awareness of tajwid in Quranic learning, due to a lack of motivation and behavioral reinforcement, has become a crucial issue, as the Quranic illiteracy rate is reaching 72.25% in Indonesia. This study aims to analyze the application of B.F. Skinner's behaviorist theory in the Tahsin Bagdadi Method to strengthen awareness of tajwid among students at the Sekolah Guru Ngaji, Pesantren Takhassus IIQ Jakarta. A qualitative descriptive method with an instrumental case study approach was used, collecting primary data through direct observation of the learning process, in-depth interviews with 1 teacher, 2 administrators, and 9 students, as well as documentation of teaching materials (Tahsin Bagdadi method book, Tajwid Poem, Teacher's Guide book). Data were analyzed through reduction, presentation, and verification. The main findings show the effectiveness of hierarchical teaching materials (from makhārij al-ḥurūf to sifat ‘āridah), repetition of i‘rāb and rhymes for habituation, as well as positive reinforcement (verbal praise) and negative reinforcement (re-explanation) that enhance motivation, discipline, focus, and reduce reading errors through operant conditioning and shaping. The conclusion states that the integration of behaviorism with Tahsin Bagdadi method successfully led to the internalization of conscious tajwid behavior. The implications include behaviorist-based teacher training and advanced mixed-methods research for broader generalization in national Quran pedagogy.